Adaptions of Lichen Microbiota Functioning Under Persistent Exposure to Arsenic Contamination - Cernava, Tomislav; Vasfiu, Qerimane; Erlacher, Armin; Aschenbrenner, Ines Aline; Francesconi, Kevin; Grube, Martin; Berg, Gabriele (Frontiers in Microbiology, 2018)
Host-associated microbiota play an important role in the health and persistence of more complex organisms. In this study, metagenomic analyses were used to reveal microbial community adaptations in three lichen samples as a response to different arsenic concentrations at the sampling sites. Elevated arsenic concentrations at a former mining site expanded the spectrum and number of relevant functions in the lichen-associated microorganisms. Apparent changes affected the abundance of numerous detoxification-related genes, they were substantially enhanced in arsenic-polluted samples. Complementary quantifications of the arsenite S-adenosylmethionine methyltransferase (arsM) gene showed that its abundance is not strictly responding to the environmental arsenic concentrations. The analyzed samples contained rather low numbers of the arsM gene with a maximum of 202 gene copies µl-1 in total community DNA extracts. In addition, bacterial isolates were screened for the presence of arsM. Positive isolates were exposed to different As(III) and As(V) concentrations and tolerated up to 30 mM inorganic arsenic in fluid media, while no substantial biotransformations were observed. Obtained data deepens our understanding related to adaptions of whole microbial communities to adverse environmental conditions. Moreover, this study provides the first evidence that the integrity of bacteria in the lichen holobiont is maintained by acquisition of specific resistances.